Single piles and pile groups under lateral loading - Reese, Lymon C., 1917- (CRC Press/Balkema, 2011)
"The field of lateral-load design is a very complex one. This book and CD-ROM not only provides the reader with an overview of procedures involved in the designing of piles and pile groups, but with a way of finding answers to related problems"-- Provided by publisher
Keywords: Piling (Civil engineering); Lateral loads.; elektronické knihy; electronic books